Patrimonialisation et politiques de la nature : le parc national de La Réunion - Igor Babou (VertigO)
The ordinary political work involved in the creation of a French national park, during the World Heritage inscription process and by its governance, leads the actors to manage with conflicting frames of knowledge, and with conceptions of their land and social relations in opposition. This work is based on “mediations” distributed at various scales: local, national and international. The field work was conducted between 2011 and 2014 among members of the French National Park of Reunion Island, inhabitants of the core area, and members of the French National Forest Office who are also inhabitants of the core area.